2014
DOI: 10.1155/2014/907316
|View full text |Cite
|
Sign up to set email alerts
|

The Takeda Three Colors Combination Test: A Screening Test for Detection of Very Mild Alzheimer’s Disease

Abstract: Background. Alzheimer's disease (AD) is the most common type of dementia and is prevalent worldwide. It is expected that AD, for which aging is a risk factor, will increase in the future. Because early detection of AD has become increasingly important, promoting demand for screening tests with adequate sensitivity. In this study, we examined the usefulness of the Takeda Three Colors Combination Test (TTCC) for screening of the very mild AD and amnestic mild cognitive impairment (aMCI). Methods. 154 senior pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…No significant difference was noted in the TTCC results between the MCI and non‐dementia groups. TTCC sensitivity for MCI was 58% according to our results, which is similar to the 47% sensitivity reported by Takeda et al . Petersen et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No significant difference was noted in the TTCC results between the MCI and non‐dementia groups. TTCC sensitivity for MCI was 58% according to our results, which is similar to the 47% sensitivity reported by Takeda et al . Petersen et al .…”
Section: Discussionsupporting
confidence: 92%
“…The probability of people without dementia exhibiting a false response on the TTCC was set at 1, and we found that people with mild dementia were 3.4‐fold more likely to exhibit a false response. Moreover, TTCC sensitivity for mild dementia was 75%, which is similar to the 76% sensitivity reported by Takeda et al . Therefore, the TTCC appears to be a useful screening tool for the early detection of dementia in Bangladesh.…”
Section: Discussionsupporting
confidence: 85%
“…Investigations of color vision using computerassisted campimetry in patients at the manifest stageThe diagram demonstrates the decrease in the number of mistakes in determining the stimulus shape on the monitor screen in comparison with the oral answers (p=0.045)CS logarithmThe number of CAG repeats in the huntingtin genePre-manifest stage Manifest stage Negative correlation between the number of CAG repeats in the huntingtin gene and the contrast sensitivity logarithm in Huntington's diseasePre-manifest HD carriers have higher values of the contrast sensitivity logarithmDiscussionColor vision disorders are known to be noted at the stage of a mild cognitive decline and to progress in Alzheimer's disease. The tests for color differentiation are considered as biomarkers of the early stage of this disease[29]. Values of color differentiation thresholds in Parkinson's disease correlate with a prominent motor dysfunction which is supposed to be associated with a common pathogenesis of motor and sensory disturbances[30].…”
mentioning
confidence: 99%